TECHNOLOGY ACCEPTANCE MODEL (TAM): THE EFFECT OF FINANCIAL LITERACY ON EFFECTIVENESS OF USING QRIS ON MSME OWNERS IN INDONESIA - Santoso, Vebrillia; Nainggolan, Romauli (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this research is to analyze the impact of Financial literacy to the effectiveness of using QRIS that Technology Acceptance Model (TAM) as moderation variable, study on MSME owners in Indonesia. This research is quantitative and involves 3 variables. The independent variable is Financial literacy, the moderating variable is Technology Acceptance Model (TAM) and the variable dependent is the Effectiveness of using QRIS. The data analysis technique for this research uses Structure Equation Modeling (SEM). The sample for this research was determined using purposive sampling, with the sample criteria being MSME owners using QRIS in micro businesses in 4 (four) cities in Indonesia. A total of 204 MSME owners using QRIS participated in the research, coming from the cities of Medan, Bali, Makassar and Bali. The research instrument used a questionnaire distributed to MSME owners. The results of this research reveal that financial literacy has a positive effect on the effectiveness of using QRIS for MSME owners in Indonesia. Second, TAM can neither strengthen nor weaken the influence of financial literacy on the effectiveness of using QRIS for MSME owners in Indonesia.